Efficacy and Safety of GHX02 in the Treatment of Acute Bronchitis and Acute Exacerbation of Chronic Bronchitis: A Phase Ⅱ, Randomized, Double-Blind, Placebo-Controlled, Multicenter Trial - Lee, Su Won; Lyu, Yee Ran; Kim, Si Yeon; Yang, Won Kyung; Kim, Seung Hyung; Kim, Ki Mo; Chae, Sung-Wook; Kang, Weechang; Jung, In Chul; Park, Yang Chun (Frontiers in Pharmacology, 2022)
Acute bronchitis and acute exacerbations of chronic bronchitis (AECB) have cough and sputum as the main symptoms with a high prevalence and substantial economic burden. Although the demand for bronchitis treatment increases due to causes, such as air pollution, the appropriateness of antibiotic prescriptions and the effects of current symptomatic treatments for bronchitis are unclear. GHX02, which is a combined formulation containing four herbs, has been clinically used for bronchitis in South Korea. We conducted a phase II, randomized, double-blind, placebo-controlled, multicenter trial to evaluate its efficacy and safety. Patients with acute bronchitis or AECB were recruited and randomized to receive high-dose GHX02 (1920 mg/day), standard-dose GHX02 (960 mg/day), or placebo for 7 days. The primary outcome measure was the change in Bronchitis Severity Score (BSS) from baseline to Day 7. The secondary outcomes were the frequency of coughing fits, Questionnaire of Clinical Symptoms of Cough and Sputum (QCSCS), Leicester Cough Questionnaire (LCQ), Integrative Medicine Outcome Scale (IMOS), and Integrative Medicine Patient Satisfaction Scale (IMPSS). A total of 117 patients were randomized to parallel groups (38 in the high-dose GHX02, 41 in the standard-dose GHX02 group, and 38 in the placebo group). The mean differences in BSS from baseline to Day 7 in the treatment groups (4.2 ± 2.0 and 4.5 ± 1.8 in the high-dose GHX02 and standard-dose GHX02 groups, respectively) were higher than the placebo group (3.8 ± 2.1), p = 0.028. The mean differences in the frequency of coughing fits from baseline to Day 7 and IMPSS were better in the GHX02 treatment group than in the placebo group (standard-dose GHX02 group vs. placebo group, p = 0.036). The QCSCS, LCQ, IMOS, and GHX02 of the treatment groups also showed more improvement than the placebo group, but there were no statistically significant differences between the groups. There were no severe adverse effects during the trial. This study supports that GHX02 is effective and safe for patients with bronchitis and provides the basis for progression to a phase III study.